Peran Brand Ambassador, Brand Image, dan Harga Terhadap Keputusan Pembelian Produk Skincare Sunscreen - Faricha Mufida Laili; Misti Hariasih; Herlinda Maya Kumalasari (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2024)
In the current era of digitalization, there are many needs from consumers that continue to increase. Beauty or skincare products are now an important need for humans. One skincare that can be used by all people is sunscreen. Sunscreen is currently a primary need that is sought after by all groups, which has made lots of sunscreen brands emerge. One of the sunscreen skincare products is Madam Gie because there are so many sunscreen brands, therefore to increase purchasing decisions can be influenced by brand ambassadors, brand image and price. This study aims to prove the existence of a positive and significant relationship between brand ambassadors, brand image and price on purchasing decisions, involving 96 respondents. Data analysis used multiple regression with the results of the study proving a positive and significant relationship between the influence of brand ambassadors, brand image and price on purchasing decisions for skin care sunscreen products. Keywords : Brand Ambassador, Brand Image, Price, Purchasing Decision